Strategies for oocyte collection and in vitro embryo production in free-roaming bison herds. Issue 1 (10th August 2022) - Zwiefelhofer, Miranda L; Shury, Todd; Zwiefelhofer, Eric M; Singh, Jaswant; Mastromonaco, Gabriela F; Adams, Gregg P
Abstract: The study was conducted to test the feasibility of protocols for field collection of cumulus–oocyte complexes (COC) for in vitro embryo production (IVP) in wild bison. The study was done with captive wood bison during the anovulatory season. In Experiment 1, the efficiency of transvaginal ultrasound-guided COC collection was compared between bison restrained in a squeeze chute without sedation vs in lateral recumbency after chemical immobilization using a dart gun ( n = 8/group). In Experiment 2, a 2 × 2 design was used to examine the effects of superstimulation treatment [single dose of equine chorionic gonodotrophin (eCG) vs multiple doses of follicle stimulating hormone (FSH)] and method of drug administration (manual injection vs field darting) on COC collection and IVP. In Experiment 1, no difference was detected between chute-restrained vs chemically immobilized groups in the time required to complete COC collections, the number of follicles aspirated (11.5 ± 1.9 vs 9.3 ± 1.8; P = 0.4) or the COC recovery rate [COC recovered/follicle aspirated; 58/92 (63%) vs 44/69 (64%); P = 0.9]. In Experiment 2, no differences were detected between superstimulation treatments (eCG vs FSH). The total number of follicles available for aspiration did not differ between manual injection and field darting (23.9 ± 2.7 vs 21.6 ± 1.9; P = 0.4). Compared with the random start unstimulated group, the embryo production rate was higher [18/132 (14%) vs 53/189 (28%); P = 0.04] after wave synchronization and superstimulation. Results suggest that COC collection is equally feasible in a recumbent position after chemical immobilization as those bison restrained in a standing position in a hydraulic chute. Ovarian superstimulation with a single-dose eCG protocol is as effective as a multiple-dose FSH protocol, and field darting is as effective as chute-side administration of superstimulation treatments. The strategies in the present study are ready to be incorporated into field collections in free-roaming bison herds.